Angiotensin Blockade Inhibits Osteopontin Expression in Non-infarcted Myocardium After Myocardial Infarction - Takanori Kusuyama; Minoru Yoshiyama; Takashi Omura; Daisuke Nishiya; Soichiro Enomoto; Ryo Matsumoto; Yasukatsu Izumi; Kaname Akioka; Kazuhide Takeuchi; Hiroshi Iwao; Junichi Yoshikawa (Elsevier, 2005)
Osteopontin has been reported to have an important role in cardiac fibrosis. However, little is known about the effects of angiotensin-converting enzyme inhibitor (ACEI) and angiotensin type 1 receptor blockers (ARB) on osteopontin expression in infarcted myocardium. The purpose of this study was to elucidate the effects of an ACEI (perindpril) and an ARB (candesartan cilexitil) on cardiac function as assessed by Doppler echocardiography and cardiac osteopontin expression associated with cardiac remodeling in myocardial infarcted rats. ACEI or ARB was administered after myocardial infarction (MI). At 4 weeks after MI, cardiac function, and mRNAs in non-infarcted myocardium were analyzed. ACEI and ARB equally prevented left ventricular dilatation, reduction of ejection fraction, and the increase in E/A wave velocity ratio and the rate of E wave deceleration by MI. ACEI and ARB significantly suppressed increased mRNA expression of atrial natriuretic peptide, brain natriuretic peptide, osteopontin, and collagen I and III in the non-infarcted ventricle at 4 weeks. Immunohistochemically stained osteopontin was increased in interstitial fibrosis of non-infarcted myocardium. Both ACEI and ARB significantly prevented cardiac fibrosis and osteopontin expression. In conclusion, angiotensin blockade inhibits osteopontin expression in non-infarcted myocardium and prevents cardiac remodeling after MI. Keywords:: osteopontin, renin-angiotensin system, cardiac remodeling, myocardial infarction